2013
DOI: 10.1080/21650373.2012.755748
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of porosity on thermal properties and fire resistance of foamed concrete

Abstract: The relationship between thermal insulation properties and porosity of fly ash based foam concrete was built, in which effective density, effective heat conductivity, and effective specific heat of fly ash based foam concrete were deduced as functions of porosity. Using the model, the effective heat conductivity of density of 580 kg/m 3 fly ash based foam concrete was the theoretically calculated as 0.145 W/(m K) while the experimental measured value was 0.142 W/(m K). The relative error of heat conductivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nevertheless, the water in foam concrete undergoes high evaporation under elevated temperature, leading to the excessive shrinkage of foam concrete [40]. Lia et al [41] concluded that foam concrete walls can provide more evacuation time under fire through numerical simulation. Elevated temperature can cause changes in the mechanical properties and stiffness of foam concrete, and even cracks.…”
Section: Elevated Temperature Resistancementioning
confidence: 99%
“…Nevertheless, the water in foam concrete undergoes high evaporation under elevated temperature, leading to the excessive shrinkage of foam concrete [40]. Lia et al [41] concluded that foam concrete walls can provide more evacuation time under fire through numerical simulation. Elevated temperature can cause changes in the mechanical properties and stiffness of foam concrete, and even cracks.…”
Section: Elevated Temperature Resistancementioning
confidence: 99%
“…The finite-discrete element technique was used to estimate the fracture energy for FC [118,171]. The heat transfer model was simulated for FC and the temperature fields were recorded for further analysis [172]. Finite element analysis also was used to model heat transfer through pixelated microstructure [173].…”
Section: Numerical Study Of Rfcmentioning
confidence: 99%